Isolation and Characterization of Diesel Oil-Degrading Pseudomonas aeruginosa (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: Diesel oil-degrading bacterium Pseudomonas aeruginosa was isolated from diesel oilpollutedsoil sample from various locations of diesel loco sheds, Vijayawada City, Andhra Pradesh, India.Materials and Methods: Two different strains having specific ability to degrade and utilize diesel oil for theirgrowth were isolated. The isolated bacterium was identified as P. aeruginosa based on its 16S rRNA typing aswell as various morphological and physiological characteristics. Results: On the basis of molecular analysis,these strains were belonged to genus Acinetobacter. Antibiotic sensitivity of the isolates was also checkedagainst different antibiotics of which they showed resistance against amoxicillin, levofloxacin, minocycline,chloramphenicol, and sulfadiazine. Conclusion: This study might be an important step toward the bioremediationof diesel oil contaminated soil and waste water.